University technology transfer: contacts and connections at the origin of licensing agreements - Rocha, António (2022)
Technology diffusion and licensing agreements between universities and industry enhance the application of research results and ensures further outcomes for the university stakeholders that take part on the technology transfer process. To this end, University technology transfer offices (TTOs) work with researchers and businesses to bring new technologies into commercialization. To get to know the Portuguese University TTOs underlying interactions and factors at the origin of licensing agreements that can create wealth for people and organizations, data has been collected among TTOs head of offices using a semi-structured survey. The most frequent knowledge exchange interactions were identified, which include: meeting with researchers to discuss the innovation potential of their work; contacting companies to discuss the development of new projects; contacts with companies known by the researchers and the researchers contact with R&D people from companies is also key on reaching licensing agreements, as well as existing collaborations with industry. The conclusions have been reached using a descriptive and exploratory approach to convey information regarding interactions at the origin of licensing agreements.